Current results and trends in platform switching - Hadi Salimi; Omid Savabi; Farahnaz Nejatidanesh (Wolters Kluwer Medknow Publications, 2011)
The platform switching (PLS) concept was introduced in the literature in 2005. The biological benefits and clinical effectiveness of the PLS technique have been established by several studies. In this article different aspects of PLS concept are discussed. Crestal bone loss, biologic width, and stress distribution in this concept are comprehensively reviewed. In this article the relative published articles from 1990 to 2011 have been evaluated by electronic search. Because of controversial results especially in immediate loading and animal studies, further modified research is needed to establish the mechanism and effect of the PLS technique. Essential changes in studies including using the control group for accurate interpretation of results and long-term observation, particularly through, randomized, prospective, multicenter trials with large numbers of participants, and implants are necessary.